Analyzing a Coursebook with International Maritime Organization-Standards and English-as-an-International-Language Principles - Rahmawati, Yusi; Fitriati, Sri Wuli; Widhiyanto, Widhiyanto; Wahyuni, Sri (Journal of English Education Program, 2025)
The practice of ESP learning in maritime colleges is heavily depended on the coursebook. This study evaluates the coursebook 'Bahasa Inggris untuk Perwira Kapal Niaga' used by nautical cadets at Politeknik Bumi Akpelni. Using Daous and Celce-Murcia (1979) checklist, this study attempt to assess the alignment of coursebook content with International Maritime Organization (IMO) standards and the principles of English as an International Language (EIL). Using a qualitative research approach, the study combined content analysis of the coursebook focusing on aspects such as linguistic accuracy, relevance of topics, integration of language skills, and intercultural elements with interviews involving lecturers, officers, and cadets. The findings reveal that while the coursebook incorporates several IMO standards, such as the language and the content, more EIL principles must be covered, particularly regarding linguistic diversity and adaptability in real-world scenarios. For instance, the coursebook lacks exposure to varied English accents, non-native speaker interactions, and culturally diverse communication contexts that cadets may encounter in multinational crews. Interviews highlighted the book"™s strengths in providing foundational maritime terminology but noted its limitations in fostering practical cross-cultural communication skills. The study emphasizes the importance of integrating EIL principles with IMO standards in maritime English education to enhance the communicative competence of future seafarers. The recommendations, including revising the coursebook to incorporate more interactive and culturally diverse exercises, can significantly improve cadets"™ preparation for global maritime operations. This research contributes to the ongoing discourse on improving maritime English education and curriculum development.